2017
DOI: 10.18357/ijih122201717784
|View full text |Cite
|
Sign up to set email alerts
|

"It's huge in First Nation culture for us, as a school, to be a role model": Facilitators and Barriers Affecting School Nutrition Policy Implementation in Alexander First Nation

Abstract: This mixed-methods community-based participatory research generated knowledge of school staff perceptions of the facilitators of and barriers to implementation of a Canadian First Nation school’s healthy nutrition policy. Themes derived from seven qualitative staff interviews were integrated with quantitative data derived from 28 staff surveys. The Medicine Wheel was used to describe results, as it provided a non-hierarchical and relational way to categorize all components and stakeholders of nutrition policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Fourteen interventions (41%) specified using participatory models of research (i.e., participatory action research and community-based participatory research) in which academic researchers and community members worked in collaboration. For example, Kipohtakaw Education Centre in Alberta developed, implemented, and evaluated both a school nutrition policy and gardening intervention through a community-based participatory research approach involving an equitable collaboration between community members and University researchers [49,51,66,67,72,88,89].…”
Section: Indigenous Control and Ownershipmentioning
confidence: 99%
“…Fourteen interventions (41%) specified using participatory models of research (i.e., participatory action research and community-based participatory research) in which academic researchers and community members worked in collaboration. For example, Kipohtakaw Education Centre in Alberta developed, implemented, and evaluated both a school nutrition policy and gardening intervention through a community-based participatory research approach involving an equitable collaboration between community members and University researchers [49,51,66,67,72,88,89].…”
Section: Indigenous Control and Ownershipmentioning
confidence: 99%
“…Survey and interview results confirmed that most students do not speak to their teachers about healthy foods, despite staff being encouraged to incorporate nutrition education in their classrooms regardless of the subject being taught. An evaluation completed with staff from KEC indicated that the policy was implemented inconsistently by staff due to their limited knowledge of the policy, competing priorities, and perceived role as nutrition policy facilitators . These findings indicate a need to encourage and support staff to improve the embedding of policy‐driven nutrition education into the classroom as part of a broader CSH approach.…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation completed with staff from KEC indicated that the policy was implemented inconsistently by staff due to their limited knowledge of the policy, competing priorities, and perceived role as nutrition policy facilitators. 21 These findings indicate a need to encourage and support staff to improve the embedding of policy-driven nutrition education into the classroom as part of a broader CSH approach. This may require explicit policy guidelines that specifically outline staff responsibilities in addition to the provision of appropriate resources and support.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen interventions (41%) specified using participatory models of research (i.e., participatory action research and communitybased participatory research) in which academic researchers and community members worked in collaboration. For example, Kipohtakaw Education Centre in Alberta developed, implemented, and evaluated both a school nutrition policy and gardening intervention through a community-based participatory research approach involving an equitable collaboration between community members and University researchers (49,51,66,67,72,88,89).…”
Section: Indigenous Control and Ownershipmentioning
confidence: 99%